2017
DOI: 10.1002/chir.22725
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CuPF6‐(S)‐BINAP loaded resin and its enantioselectivity toward phenylalanine enantiomers

Abstract: A type of resin-anchored CuPF -(S)-BINAP was synthesized and identified. The PS-CuPF -(S)-BINAP resin was used to adsorb the phenylalanine enantiomers. The results showed that the adsorption capacity of PS-CuPF -(S)-BINAP resin toward L-phenylalanine was higher than that of resin toward D-phenylalanine. PS-CuPF -(S)-BINAP resin exhibited good enantioselectivity toward L-phenylalanine and D-phenylalanine. The influence of phenylalanine concentration, pH, adsorption time, and temperature on the enantioselectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Recently, some diphosphine ligands used as chiral catalysts in asymmetric reactions have been proved to be effective chiral selectors in enantioselective liquid‐liquid extraction (ELLE) . For instance, ( S )‐BINAP‐metal, ( S )‐MeO‐BIPHEP‐metal, and ( S )‐SEGPHOS‐metal complexes have considerable abilities to separate amino acid and mandelic acid enantiomers . Since the chiral ligands in asymmetric reactions may be the good chiral selectors, it seemed interesting to further study this field with the goal of finding more ligands with favorable enantiomeric recognition and separation potency in ELLE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some diphosphine ligands used as chiral catalysts in asymmetric reactions have been proved to be effective chiral selectors in enantioselective liquid‐liquid extraction (ELLE) . For instance, ( S )‐BINAP‐metal, ( S )‐MeO‐BIPHEP‐metal, and ( S )‐SEGPHOS‐metal complexes have considerable abilities to separate amino acid and mandelic acid enantiomers . Since the chiral ligands in asymmetric reactions may be the good chiral selectors, it seemed interesting to further study this field with the goal of finding more ligands with favorable enantiomeric recognition and separation potency in ELLE.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] For instance, (S)-BINAP-metal, (S)-MeO-BIPHEP-metal, and (S)-SEGPHOS-metal complexes have considerable abilities to separate amino acid and mandelic acid enantiomers. [16][17][18] Since the chiral ligands in asymmetric reactions may be the good chiral selectors, it seemed interesting to further study this field with the goal of finding more ligands with favorable enantiomeric recognition and separation potency in ELLE.…”
Section: Introductionmentioning
confidence: 99%
“…This result revealed that citric acid was successfully anchored on resins. In addition, the absorption band in the vicinity of 678 cm −1 still existed in curves a1, which indicated that the –Cl groups were not fully substituted by citric acid during the reaction [ 17 , 18 ]. Curves b1, b2 and b3 in figure 3 are the FTIR spectra of PS-Cl, PS-OH and PS-O-CA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Verkuijl et al and Tang et al have reported that (S)-BINAP-metal complexes exhibited good abilities to separate amino acid enantiomers. 7,[16][17][18][19][20][21][22] And our precious works also revealed that (S)-MeO-BIPHEP and (S)-SEGPHOS have good abilities to recognize amino acid enantiomers. 23 These results indicated that chiral diphosphine ligands are excellent chiral extractants in enantioselective liquid-liquid extraction.…”
Section: Introductionmentioning
confidence: 84%
“…1,2 Tartaric acid, 3 crown ether, 4 cyclodextrin, 5 cinchona alkaloid, 6 and metal complex 7 are common chiral extractants that are widely used in enantioselective liquid-liquid extractions. 7,[16][17][18][19][20][21][22] And our precious works also revealed that (S)-MeO-BIPHEP and (S)-SEGPHOS have good abilities to recognize amino acid enantiomers. (S)-BINAP, (S)-MeO-BIPHEP, and (S)-SEGPHOS are important chiral catalysts that are widely used in asymmetric reactions.…”
Section: Introductionmentioning
confidence: 94%